Pengaruh Diferensiasi Produk dan Citra Merek Terhadap Minat Beli Ulang Produk Scarlett Whitening - Tampubolon, Rhoni Ilham (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The purpose of this study was to determine "The Effect of Product Differentiation and Brand Image on Interest in Buying Scarlett Whitening Products (Case Study of Scarlett Body Lotion Products in the People of Pematang Jaya Langkat District)". two variables, where the variable is measured by a Likert scale. The population in this study were 366 people who were female with a sample of 191 respondents taken from part of the existing population. And by using the Slovin formula technique. Data processing was carried out using SPSS 24 software. The results of this study indicate that the Effect of Product Differentiation and Brand Image partially has a positive and significant effect on repurchase interest in Scarlett Whitening Products (Case Study of Scarlett Body Lotion Products in the People of Pematang JayaLangkat District). Product differentiation and brand image simultaneously have a positive and significant effect on repurchase interest in Scarlett Whitening Products (Case Study of Scarlett Body Lotion Products in the People of Pematang Jaya Langkat District).